2008
DOI: 10.1152/ajpgi.00585.2007
|View full text |Cite
|
Sign up to set email alerts
|

TNBS-induced inflammation modulates the function of one class of low-threshold rectal mechanoreceptors in the guinea pig

Abstract: The effects of trinitrobenzene sulfonic acid (TNBS)-induced inflammation on specialized, low-threshold, slowly adapting rectal mechanoreceptors were investigated in the guinea pig. Under isoflurane anesthesia, 300 microl saline or TNBS (15 mg/ml) in 30% ethanol was instilled 7 cm from the anal sphincter. Six or 30 days later, single unit extracellular recordings were made from rectal nerve trunks in flat-sheet in vitro preparations attached to a mechanical tissue stretcher. TNBS treatment caused macroscopic ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
3
11
0
Order By: Relevance
“…Histological pathology in the acute phase includes ulceration, goblet cell depletion, oedema and increased granulocyte activity. 54,55,57,[61][62][63][64][65][66][67] The inflammatory aspects resulting from TNBS instillation are predominantly mediated by a Th1 pro-inflammatory cytokine response, consistent with clinical PI-IBS observations. 68 Despite the close correlation between results obtained using TNBS across several species, several considerations must be made prior to treatment.…”
Section: Visceral Hypersensitivity and Tnbssupporting
confidence: 74%
See 1 more Smart Citation
“…Histological pathology in the acute phase includes ulceration, goblet cell depletion, oedema and increased granulocyte activity. 54,55,57,[61][62][63][64][65][66][67] The inflammatory aspects resulting from TNBS instillation are predominantly mediated by a Th1 pro-inflammatory cytokine response, consistent with clinical PI-IBS observations. 68 Despite the close correlation between results obtained using TNBS across several species, several considerations must be made prior to treatment.…”
Section: Visceral Hypersensitivity and Tnbssupporting
confidence: 74%
“…A milder sensitization was observed in those afferents that respond to light mucosal stroking (mucosal afferents), whereas those afferents that respond with low thresholds to circular stretch (muscular afferents) are not affected in either mouse or guinea-pig models. 55,63 Remarkably, afferents residing in the outer wall of the colon, furthest from the site of damage, show the greatest changes.…”
Section: Post-infectious Ibsmentioning
confidence: 99%
“…This suggests that in order to observe upregulation of mechanosensory mechanisms, the choice of species and/or the inflammatory agent is important. Our recent study in the guinea-pig24 showed, in a TNBS model, that rectal muscular afferents were sensitised to distension in the acute phase of inflammation, but unaffected after recovery. In this case our stimulus is the same but the species is different, but there is agreement that long-term changes in mechanosensitivity are absent in low-threshold distension-sensitive subtypes of afferents.…”
Section: Discussionmentioning
confidence: 93%
“…including those at day 10 where overall differences were not seen). Recent studies suggest important differences may exist between specific fibre types and pelvic compared to splanchnic nerves in response to inflammation (Lynn et al 2008; Hughes et al 2009). A previous study of intestinal afferents has also shown a correlation between mechanosensitivity and neuronal hyperexcitability (Keating et al 2008), although the current study is the first to identify one of the candidate ion channels (i.e.…”
Section: Discussionmentioning
confidence: 99%